PERFORMANCE MEASUREMENT OF PHARMACY DEPARTMENT AT PANEMBAHAN SENOPATI BANTUL REGIONAL GENERAL HOSPITAL USING BALANCED SCORECARD - Gusti Ayu Putu Sri Erwinayanti; Achmad Purnomo; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
Pharmacy Department is the highest revenue of Panembahan Senopati Bantul Regional General Hospital, but its performance is never measured, so the success of intangible and tangible asset management in achieving the organisational vision and goals is still unknown. This research was conducted to measure and evaluate the performance of Pharmacy Department at Panembahan Senopati Bantul Regional General Hospital using the balanced scorecard. This research was a descriptive non-experimental study. Data were obtained retrospectively and prospectively. Qualitative data were acquired through questionnaires and in-depth interview with Head of the Pharmacy Department. Quantitative data were attained through direct observation, prescription survey, and financial reports. Quantitative data were statistically analyzed using a statistic, while qualitative data were analysed and presented in descriptive form. Performance of learning and growth perspective showed that from human capital view, the proportion of pharmacists and bed was not ideal (1:36); the percentage of employee training had not reached 100%; and the average of employee morale was high (3.18). The percentage of Organization Capital was 75.71% which showed the high culture, leadership, teamwork, and alignment. Meanwhile, Information System Capabilities needed the addition of expired date and drugs dosage databases, internet, and the development of management information system. The performance of internal business process perspective showed that the average of drug availability was 98%; the average dispensing time was 37 minutes for compounded prescription and 29 minutes for non compounded prescription; the average SOP suitability with accreditation standards of hospital was 74%; and there was no documentation for medication error. Performance of the customer’s perspective showed the percentage of patients encountered was 80.97%; the rate of customer satisfaction was 86%; and the rate of customer growth was 1% per month. Performance of the financial perspective found that TOR value was 9 times per year in 2011 and 7 times per year in 2012; the rate of service revenue in 2011 was 35% and 28.35% in 2012; Gross Profit Margin was 26.29% in 2011 and 24.83% in 2012.Keywords: Performance, Balanced Scorecard, Pharmacy Department